Global Burden and Challenges of Melioidosis - Dance, David AB (MDPI - Multidisciplinary Digital Publishing Institute, 2019)
This book is the definitive reference regarding the global status of melioidosis in 2018. Melioidosis is one of the most neglected tropical diseases (NTDs), so much so that it is not even included in the WHO list of NTDs. Yet modeling suggests that it kills more people worldwide every year than diseases that are much better known, such as leptospirosis and dengue. The reasons for this under-recognition are numerous, including the fact that it mainly affects the disadvantaged rural poor in areas that are poorly supplied with the diagnostic capability to make the diagnosis. In 22 separate articles, expert authors from around the world have summarized what is known about the burden of the disease in humans and animals and the presence of the causative bacterium in the environment in their countries or regions. They have also identified the main obstacles and challenges to establishing the true burden, and to ensure that patients receive accurate diagnosis and optimal care for this all too frequently fatal disease. Rather than focusing on the theoretical risk of the use of Burkholderia pseudomallei as a biological weapon, this book highlights its importance as a clear and present danger to global public health.